Experimental and Numerical Studies on Gas Production from Methane Hydrate in Porous Media by Depressurization in Pilot-Scale Hydrate Simulator - Li, Gang; Li, Bo; Li, Xiao-Sen; Zhang, Yu; Wang, Yi (Energy & Fuels, 2012)
Dissociation processes of methane hydrate in porous media using the depressurization method are investigated by a combination of experimental observations and numerical simulations. In situ methane hydrate is synthesized in the Pilot-Scale Hydrate Simulator (PHS), a three-dimensional (3D) 117.8-L pressure vessel. During the experiment, constant-pressure depressurization method is used during the hydrate dissociation. A vertical well at the axis of the PHS is used as the production well. The initial hydrate and aqueous saturations before dissociation are S-H0 = 27% and S-A0 = 37% in volume, respectively. The hydrate dissociates continuously under depressurization and there is little hydrate remaining in the PHS. The hydrate dissociation is an analog of a moving boundary ablation process, and the hydrate dissociation interface separates the hydrate dissociated zone containing only gas and water from the undissociated zone containing the hydrate. The temperature increases in the hydrate dissociated zone near the boundaries, while that in the hydrate undissociated zone around the PHS center basically remains constant. The numerical results of the cumulative gas produced, the remaining hydrate in the deposit, and the temperature spatial distribution all agree well with the experiments, which completes the validation of the mathematical model and numerical codes employed in this study. The heat transfer from the surroundings is predominant in our experimental and numerical cases. The analysis of sensitivity to the intrinsic permeability and the initial hydrate saturation of the numerical simulation are investigated.